The effect of preceding sequences on stock returns - Andrey Kudryavtsev (European Financial and Accounting Journal, 2017)
This study explores the effect of the gambler's fallacy on stock returns. I hypothesize that if during a number of consecutive trading days, a stock's return is positive (negative), then due to the gambler's fallacy, at least some of the investors may believe that the stock's price "has" to subsequently fall (rise), and thus, to increase their willingness to sell (buy) the stock, resulting in negative (positive) abnormal market-adjusted stock returns. Employing a large sample of daily stock price data, I was able to document that following relatively long sequences of positive (negative) stock returns, abnormal stock returns are on average significantly negative (positive), indicating the existence of the price pressure towards the return sign reversal. Moreover, the magnitude of the effect is stronger for longer return sequences. The effect is found to be more pronounced for smaller and more volatile stocks, and is robust to other relevant company - and stock-specific factors.
Keywords: G11; G12; G19; 650; Abnormal Stock Returns; Gambler's Fallacy; Investment Decisions; Price Reversals; Stock Return Sequences